CFD-modelling of Selective Non-Catalytic Reduction of NOx in grate-kiln plants. (27th September 2010) - Burstrom, Per E.C.; Lundstrom, T. Staffan; Marjavaara, B. Daniel; Toyra, Simon
The overall goal of this project is to find out if Selective Non-Catalytic Reduction (SNCR) technologies can be used in grate-kiln plants for NOx reduction. The technique has, to the best knowledge of the authors, never been used in this context before, despite that it is commonly used in cement and waste incineration plants. A model for spray injection into the grate was included in the model enabling a study of the overall mixing between the injected reagent droplets and the NOx polluted air. The simulations indicate that the SNCR-technique works with urea, but not with ammonia.